PERAN GURU DALAM PENDIDIKAN KARAKTER RELIGIUS PADA ANAK USIA DINI - Masliani; Novitawati; Yogi Prihandono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teachers play an important role in shaping religious character in students. The school environment is a means of implementing character education because most children spend their time at school so that something they get at school will affect the development of children's character. The teacher's obligation as an educator is to plan, implement, assess, and evaluate quality learning is to provide education to children starting from an early age. Teachers as models for children both from positive and negative aspects and also provide a picture of life for students. This paper aims to describe religious character and describe how the role of teachers as educators in educational institutions in building religious character education for early childhood. This study uses a literature study method whose data sources are relevant and related to the role of teachers in religious character education for early childhood. The results of the study show that religious character is interpreted as an attitude or behavior that is obedient in carrying out the teachings of the religion that is believed, tolerant of the implementation of worship, and living in harmony with others. The role of teachers in early childhood religious character education can be seen from the strategies that teachers can apply to shape children's religious character including developing religious culture routinely in ordinary learning days, creating an educational institution environment that supports religious education, delivering formal education in learning with religious subject matter, and creating a religious situation or condition. Religious character education must be arranged in such a way that it will run according to the expected goals. To plan an instillation program, synergy is needed between parents, educators, and leaders in an institution.